2017
DOI: 10.3233/nre-172248
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Endurance Test (d2): Normative data for Spanish-speaking pediatric population

Abstract: Abstract. OBJECTIVE:To generate normative data for the Concentration Endurance Test (d2) in Spanish-speaking pediatric populations. METHOD:The sample consisted of 4,373 healthy children from nine countries in Latin America (Chile, Cuba, Ecuador, Guatemala, Honduras, Mexico, Paraguay, Peru, and Puerto Rico) and Spain. Each participant was administered the d2 test as part of a larger neuropsychological battery. The Total number of items processed (TN), Total number of correct responses (CR), Total performance (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
(30 reference statements)
1
5
0
2
Order By: Relevance
“…In a multicentric study children from Mexico, Puerto Rico, and Spain where the parents had a mean level of parental education (MLPE) >12 years obtained higher d2 TOT scores than children whose parents had a MLPE ≤12 years. They found that a child's gender did not affect the d2 TOT scores for any country (Rivera et al, 2017). In line with this, we found lower scores in both CP in the d2 test and PMMA in Chilean children.…”
Section: Context and Musical Experience Influencesupporting
confidence: 90%
“…In a multicentric study children from Mexico, Puerto Rico, and Spain where the parents had a mean level of parental education (MLPE) >12 years obtained higher d2 TOT scores than children whose parents had a MLPE ≤12 years. They found that a child's gender did not affect the d2 TOT scores for any country (Rivera et al, 2017). In line with this, we found lower scores in both CP in the d2 test and PMMA in Chilean children.…”
Section: Context and Musical Experience Influencesupporting
confidence: 90%
“…For psychosocial assessment the following tests were used: Children Depression Inventory [35] (CDI), Revised Children's Manifest Anxiety Scale [36] (CMAS-R), Pediatric Quality of Life Inventory [37] (PedsQL) Parent-Report, and Adaptive Behavior Assessment System, Second Edition [38] (ABAS-II). All of these tests had normative data available for Spanish-speaking children and adolescents [39][40][41][42][43][44][45][46][47][48].…”
Section: Neuropsychological Evaluationmentioning
confidence: 99%
“…The participant is asked to scan the lines from left to right and cross out all "d"s with two dashes within a time limit of 20 seconds per line. There are extensive norms based on clinical and nonclinical populations from Europe (Brickenkamp and Zillmer 1998;Rivera et al 2017) that have been extended to populations in other regions. Several studies have demonstrated that the D2 is highly reliable (Brickenkamp and Zillmer 1998;Lee et al 2018;Steinborn et al 2018) and that it shows good construct validity (Bates and Lemay 2004;Wassenberg et al 2008).…”
Section: Introductionmentioning
confidence: 99%